Effect of Transformational Leadership and Organizational Citizenship Behavior: Determining the Roles of Supervisor Identification, and Self-determination in the Automobile Industry - Zheng, Zhou; Segumpan, Reynaldo Gacho (South Asian Journal of Social Sciences and Humanities, 2024)
Background and Purpose: The present study analyses the impact of transformational (TL), transactional (TRL) and laissez-faire styles (LSF) of leadership on Organizational Citizenship Behavior (OCB) of employees in the context of the automobile industry. Moreover, the study also focuses on the mediating effect of self-determination (SDE) and the moderating role of supervisor identification (SD) on the proposed correlation. Method: The primary data for the study was collected by designing a survey questionnaire. The questionnaires were distributed among the employees from the automobile industry and a final sample of 312 responses was utilized. The data was analyzed through the application of PLS-SEM. Findings: The study validated a positive and significant relationship between LSF and OCB. Similarly, TRL and OCB were positively and significantly related. Notably, TL was an insignificant predictor of OCB. SD exerted a significant moderating role in the association between TRL and SDE only. The evaluation of the mediating role of SDE in the association between leadership styles and OCB revealed that SDE significantly mediated the association between TL and OCB, and TRL and OCB. Nevertheless, SDE was an insignificant mediator in the association between LSF and OCB. Conclusion and Implications: Thus, the findings of the present study hold significance for leaders from automobile industry leaders and offer guidance to design strategies for enhancing the OCB and workplace engagement through effective leadership strategies.